The modified elevated gap interaction test: a novel paradigm to assess social preference - Chris I. de Zeeuw; Si-yang Yu; Jiawei Chen; Willem S. van Hoogstraten; Arn M. J. M. van den Maagdenberg; Laurens W. J. Bosman; Lieke Kros (Open Biology)
Social deficits play a role in numerous psychiatric, neurological and neurodevelopmental disorders. Relating complex behaviour, such as social interaction, to brain activity remains one of the biggest goals and challenges in neuroscience. Availability of standardized tests that assess social preference is however, limited. Here, we present a novel behavioural paradigm that we developed to measure social behaviour, the modified elevated gap interaction test (MEGIT). In this test, animals are placed on one of two elevated platforms separated by a gap, in which they can engage in whisker interaction with either a conspecific or an object. This allows quantification of social preference in real interaction rather than just proximity and forms an ideal setup for social behaviour-related neuronal recordings. We provide a detailed description of the paradigm and its highly reliable, deep-learning based analysis, and show results obtained from wild-type animals as well as mouse models for disorders characterized by either hyposocial (autism spectrum disorder; ASD) or hypersocial (Williams Beuren syndrome; WBS) behaviour. Wild-type animals show a clear social preference. This preference is significantly smaller in an ASD mouse model, whereas it is larger in WBS mice. The results indicate that MEGIT is a sensitive and reliable test for detecting social phenotypes.